Women, Identity Development and Spirituality within the Anglican Church of Canada: A Phenomenological Study - Richey, Meghan (Université Saint-Paul / Saint Paul University, 2018)
Identity development has been an active area of research in the field of psychology for many years. This Master’s thesis will present results from a study investigating the interplay of gender and spirituality in the identity development of women within the context of the religious institution of the Anglican Church of Canada. Previous scholarship has indicated the potentially harmful impacts of traditionally patriarchal religious institutions on women’s identity and spiritual development, indicating the need for further exploration. The sample for this study included twelve participants who self-identified as women, practicing Christians and members of the Anglican Church of Canada. Interpretive phenomenological analysis and semi-structured interviews were used to investigate the experiences and meaning making of the participants with regards to their identity development within their religious contexts. Specifically, the relationship between identity development, gender and spirituality were explored, in order to better understand the influence of these phenomena on each other and to map a process of identity development that may be particular to women. While each woman’s story was unique, emergent themes generated a tentative model that captured characteristics of the participants’ experiences that were recurrent across interviews. Analysis revealed a framing theme of intergenerational journey, and the superordinate themes of disruption in integration, differentiation, and authenticity in integration, as well as several subordinate themes. This study points to the importance of considering gender identity and spirituality as interactive factors in identity development, and the value of hearing women’s voices as essential to gaining access to, and a deeper understanding of, women’s experiences.
Keywords: gender; spirituality; identity development; women